An Embedded Communication System Solution for Operation in the Presence of RF Noise and Interference - Tasci, Burak; Erol, Yavuz (Horizon House Publications Inc, 2023)
A secure communication system with a spectrum scanning feature is realized with a programmable system-on-chip (PSoC) embedded system platform. The development of this complex electronic system is possible due to the fast data processing and internal signal processing capabilities provided by PSoC controllers. This PSoC-based communication system can operate in an environment with intense channel noise and external disrupting RF signals through the transmission of data packets from different channels whose frequencies change dynamically with time. It enables emergency communication with specialized hardware and a unique algorithm.